Polygenic determinants of White Matter Hyperintensities and sex‐specific genetic profiles in the Alzheimer's continuum. (20th December 2022) - Genius, Patricia; Rodríguez‐Fernández, Blanca; Operto, Grégory; Falcon, Carles; Minguillón, Carolina; Fauria, Karine; Molinuevo, Jose Luis; Esteller, Manel; Guigó, Roderic; Zetterberg, Henrik; Blennow, Kaj; Sudre, Carole H; et al.
Abstract: Background: Recent genetic association studies suggested the polygenic contribution to white matter hyperintensities (WMH). The aim of this study was to provide a genetic characterization of WMH in middle‐aged cognitively unimpaired individuals at higher risk of Alzheimer's disease (AD) by investigating whether the genetic predisposition to specific complex diseases is associated with WMH and whether these effects are sex‐specific and dependent on core AD CSF biomarker levels. Method: A total of 497 cognitively unimpaired middle‐aged participants at risk of AD were included (63.2% of women). A subgroup of 288 individuals also had available information on CSF biomarkers measured using the Elecsys ® and the exploratory Roche NeuroToolKit immunoassays. We classified individuals in groups defined by their biomarker profile (A/T framework). Genetic predisposition was calculated through polygenic risk scores (PRS), estimated from the most recent genome‐wide association meta‐analyses for cerebrovascular/vascular, neurodegenerative, and AD‐related biomarkers. WMH volumes were quantified through fluid‐attenuated inversion recovery (FLAIR) images obtained from magnetic resonance scans. We used non‐parametric Spearman's rank tests to assess the association between global WMH volumes and PRSs (nominal p‐value < 0.05). Models stratified by sex and A/T group were assessed to discern WMH sex‐specific genetic differences and to discriminate genetic profiles associated with WMH in the earliest stages of the Alzheimer's continuum . Result: Genetic predisposition to small vessel disease was positively correlated with volumes of WMH only in women [Figure 1]. Furthermore, only for A+T‐ individuals, we found that genetic predisposition to higher CSF interleukin 6 levels and cerebral infarction was positively correlated with WMH volumes. Moreover, genetic predisposition to abnormal CSF p‐tau levels and AD was negatively correlated with volumes of WMH. We did not find significant results neither in A+T+ nor in A‐T‐ individuals. Conclusion: Sex differences were found suggesting better genetic predictability of cerebrovascular‐PRSs to assess WMH in women. Results by A/T group suggested that asymptomatic individuals that are amyloid‐β‐positive but tau‐negative (A+T‐) have several differential genetic patterns associated with WMH that were not significant in the other groups. Overall, these findings may lead to sex differences and different biological mechanisms affecting WMH in the Alzheimer's continuum .